PROFIL USAHA SELAI NANAS â€œCAP BURUNG MALEOâ€ UD ASLI TOTABUAN DI KELURAHAN MOTOBOI KECIL KOTA KOTAMOBAGU - Dini ., Budihastuti; Theodora M. Katiandagho; Noortje M. Benu (AGRI-SOSIOEKONOMI, 2016)
The purpose of this research is to describe the Profile of Pineapple Jam Business â€œCap Burung Maleoâ€ UD Asli Totabuan especially in the raw materials supplying aspect, management, marketing, also the profits of pineapple jam production. This research has been carried out for three months, from April until June 2016. Data used in this research is primary data that collected from UD Asli Totabuan and primary data obtained from interview with the Owner of UD Asli Totabuan. Analysis used in this research is Profits analysis, revenue, Break Even Point (BEP), to find out the profits and revenue of UD Asli Totabuan. Based on the research result, UD Totabuan in the pineapple jam production only producing once or twice in a year, on the pineapple harvest season and when there is no price spike, raw materials obtained from farmers in the West Passi and Lobong. The Industry management of UD Totabuan is simple doesnâ€™t use the management functions like planning, organizing, actuating, and controlling. The Marketing channels of UD Asli Totabuan is two which from Producer to Producer and Producer to Retailer, Retailer to consumer. The profits of Pineapple jam business by UD Totabuan Cap Burung Maleo for March 2016 is Rp. 9.625.828,*ls*Keywords: Pineapple Jam, â€œCap Burung Maleoâ€, Motoboi Kecil Village, Kotamobagu City